Status, Challenges and Opportunities of Montane Forest Resource of Ethiopia: From Conservation Point of View - Kuture, Markos Kuma (Indian Forester, 2017)
Montane forests of Ethiopia are home to many people and different wild animals, birds, micro-fauna and provide diverse goods and services to the mankind. Even though it gives a lot services and goods for human beings, conservation, managements and protection efforts of forests are inadequate. This is basically due to lack of implementation of forest laws and principles at ground level. The difficulty of implementation of the laws is due to lack of integration of different sectors, checkpoint at different parts of the country to control the illegal movement of forest products and awareness that means laws and principles are not properly known among the various stakeholders at all level. Besides, understanding preconditions and accepting them unconditionally for co-management arrangement is essential. An important precondition to a successful co-management arrangement principles are recognition of community rights to ownership of forest resources, participation of community on existing formal and informal social structures, and consideration for sharing of benefits. Therefore, the present communication compressed of montane forest types, conservation status, and impacts of anthropogenic activities, products and services to them.